Pelatihan Budidaya Cabai Polibag untuk Pemberdayaan dan Ketahanan Pangan di Pematang Gubernur - Supardi, Nurul Iman; Amri, Khairul; Witanto, Yovan; Zuliantoni, Zuliantoni (Dharmakayana, 2025)
This community service activity aims to improve community food security through the implementation of chili cultivation in polybags in Pematang Gubernur Village, Muara Bangkahulu District, Bengkulu City. The main problems faced by the community at the partner location are limited yard space and high chili prices during certain seasons. Through chili cultivation training in polybags, the community is equipped with knowledge and practical skills ranging from preparing the planting medium, sowing seeds, planting, maintenance, and harvesting. Implementation methods include counseling, live demonstrations, and field assistance. The results of the activity show an increase in community knowledge and motivation in utilizing limited land to grow chili independently. Thus, this activity contributes to supporting household food security and community economic empowerment.